TRANSFORMATION OF PUBLIC SERVANTS THROUGH THE USE OF LOCAL GOVERNMENT INFORMATION SYSTEM APPLICATIONS AT THE BAUBAU CITY DPRD SECRETARIAT OFFICE - La Didi; Rahmawati; Samsina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study investigates the transformation of public services through the implementation of the Regional Development Planning Information System (SIPD) application at the Secretariat of the Regional People's Representative Council (DPRD) of Baubau City. Preliminary findings suggest that the adoption of SIPD has driven a shift towards more digital, efficient, and transparent administrative processes, supported by the availability of technology infrastructure, improved human resource competencies, and data security effectiveness. However, realizing the full potential of SIPD for the optimization of public services requires continuous strengthening of these three crucial aspects. Inadequate technological infrastructure, human resource competency gaps, and hybrid data management are critical areas of intervention to ensure the sustainability of digital transformation. The implications of this study confirm the need for technological infrastructure updates, adaptive training programs, and comprehensive integration of data management systems to strengthen security and efficiency. Further studies are recommended to quantify the impact of this transformation as well as explore innovative strategies for hybrid legislative data management to identify best practices and improve comprehensive security.